1960
DOI: 10.1021/jf60112a023
|View full text |Cite
|
Sign up to set email alerts
|

Meat Flavor Chemistry, Precursors of Beef Flavor

Abstract: odor detected. Reducing sugars, present in muscle, could react with protein and possibly produce the observed aromas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1964
1964
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…A number of model systems have been developed for studying meat flavor or producing synthetic meatlike complexes (Batzer et al, 1960(Batzer et al, , 1962Hsieh et al, 1980a;Schroedter and Wolm, 1980). Most of these have consisted of a reducing sugar, usually glucose, a source of amino acids, and flavor enhancers, such as inosine monophosphate (IMP).…”
Section: Origi N Of Meat Y Flavo Rmentioning
confidence: 99%
“…A number of model systems have been developed for studying meat flavor or producing synthetic meatlike complexes (Batzer et al, 1960(Batzer et al, , 1962Hsieh et al, 1980a;Schroedter and Wolm, 1980). Most of these have consisted of a reducing sugar, usually glucose, a source of amino acids, and flavor enhancers, such as inosine monophosphate (IMP).…”
Section: Origi N Of Meat Y Flavo Rmentioning
confidence: 99%
“…Certain precursors of cooked beef flavor and odor are extractable with cold water (Hornstein et aZ., 1960;Batzer et al, 1960). Many of the cooked-beef flavor and odor precursors are low-molecular-weight compounds that diffuse through cellulose dialysis membranes.…”
mentioning
confidence: 99%
“…Many of the cooked-beef flavor and odor precursors are low-molecular-weight compounds that diffuse through cellulose dialysis membranes. Dialysis techniques were first used in this type of study by , and later by other investigators (Batzer et al, 1960(Batzer et al, , 1962. The latter investigators used dialysis techniques to isolate a fraction from cold-water extracts of beef that contained glucose, inosinic acid, and an unknown glycoprotein.…”
mentioning
confidence: 99%
“…Two main approaches have generally been utilized in studying meat flavor: (1) identification of the volatiles released from meat during the cooking process (Minor et al 1965;Persson and von Sydow 1973); and (2) determining possible flavor precursors by fractionation of muscle components followed by sensory evaluation of the isolated fractions (Batzer et al 1960;Wasserman and Gray 1965). More recently, evaluation of possible chemical components for their similarity to meat aroma at different concentrations and then predicting their optimum concentrations and sensory scores has proven to be valuable for determining their contribution to meat flavor (Hsieh et al 1980a;Bodrero et al 1981).…”
Section: Flavor Of Meat Basic Chemistrymentioning
confidence: 99%
“…Lysine, which has also been demonstrated to be involved in development of browning products on heating of muscle proteins (MilleretaL 1965a,b;Skurray and Cumming 1974) andmay be involved in development of meat flavor, is found in considerable amounts in myosin and connectin with other lesser but important contributors being M-protein and C-protein. Batzer et al (1960; demonstrated that the precursors for meat flavor included glucose, a glycoprotein and inosinic acid. Hsieh et al (1980a) in developing a model meat flavor system utilized gelatin as the glycoprotein in addition to reducing sugars and amino acids, and found that gelatin played an important role in giving the synthetic mixture "mouthfeel."…”
Section: Role Of Different Muscle Proteinsmentioning
confidence: 99%